A Novel Contact Lens Sensor System for Continuous Intraocular Pressure Monitoring: Evaluation of Accuracy in Human Eyes - Yifan Wei, MM; Yuning Zhang, PhD; Zidong Chen, PhD; Jones Iok-Tong Chong, ME; Christopher Ching Hymn Lee, PhD; Isuru Kaweendra Karunaratne, PhD; Xinyi Zhang, PhD; Mingjie Deng; Yangfan Yang, MD, PhD; David C.C. Lam, PhD; Minbin Yu, MD, PhD (Ophthalmology Science)
Purpose: To evaluate the accuracy of intraocular pressure (IOP) monitoring by a novel contact lens sensor system (CLS) in human eyes. Design: Cross sectional study. Participants: Eighty eyes of 80 participants were recruited and divided into 3 groups: (1) 40 normal eyes; (2) 30 eyes with primary open-angle glaucoma (POAG) or ocular hypertension (OHT) with normal IOP (<21 mmHg), including 27 POAG eyes and 3 OHT eyes; and (3) 10 POAG/OHT eyes with high IOP (≥21 mmHg), comprising 4 POAG eyes and 6 OHT eyes. Methods: Participants wore the CLS to enable continuous monitoring of IOP while they assumed both seated and supine positions, with each position maintained for 10 minutes. Intraocular pressure was also measured by the Goldmann applanation tonometer (GAT) while participants were seated and the Perkins applanation tonometer (PAT) in supine, both before and after CLS wear. Main Outcome Measures: The average IOP measured by CLS during the final 1-minute of seated and supine positions was compared with IOP measured by GAT and PAT before and after CLS wear. Also, intraclass correlation coefficient and Bland–Altman analyses were performed. Results: No significant differences were found between pre-CLS GAT and CLS in normal eyes or between all comparisons in POAG/OHT eyes with high IOP (P > 0.5). Contact lens sensor system IOP was higher than pre-CLS PAT and post-CLS GAT/PAT IOP in normal eyes (P < 0.01), and higher than pre-CLS GAT and post-CLS PAT in POAG/OHT eyes with normal IOP (P < 0.05). All IOP differences were within ± 2 mmHg. Intraclass correlation coefficient showed moderate to very strong consistency (0.51 ≤ r ≤ 0.95, P < 0.05) except for that between sitting CLS and post-CLS GAT in POAG/OHT eyes with high IOP. Bland–Altman analysis showed that over 80% of points were within ± 5 mmHg and over 60% within ± 3 mmHg. Conclusions: With good agreement in IOP measurement compared with applanation tonometry in seated and supine positions, across normal and POAG/OHT eyes, the CLS can be used for fairly accurate continuous IOP monitoring. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.